Principles of engineering mechanics - Harrison, H. R. (Butterworth Heinemann, 1994)
Students of engineering mechanics require a treatment embracing principles, practice an problem solving. Each are covered in this text in a way which students will find particularly helpful. Every chapter gives a thorough description of the basic theory, and a large selection of worked examples are explained in an understandable, tutorial style. Graded problems for solution, with answers, are also provided. Integrating statistics and dynamics within a single volume, the book will support the study of engineering mechanics throughout an undergraduate course. The theory of two- and three-dimensional dynamics of particles and rigid bodies, leading to Euler's equations, is developed. The vibration of one- and two-degree-of-freedom systems and an introduction to automatic control, now including frequency response methods, are covered. This edition has also been extended to develop continuum mechanics, drawing together solid and fluid mechanics to illustrate the distinctions between Eulerian and Lagrangian coordinates. Supports study of mechanics throughout an undergraduate course Integrates statics and dynamics in a single volume Develops theory of 2D and 3D dynamics of particles and rigid bodies.